Un résumé des lignes de force du système monétaire international actuel - Leroy, Vély (L'Actualité économique, 1979)
In this paper the author outlines the forces underlying the present international monetary system. Since creation, in Bretton Woods, of the International Monetary Fund, two important amendments have been brought to the statutes of this institution. First, in July 1969, a Special Drawing mechanism was created; second, following the April 1978 amendment, the Special Drawing Right system is no longer based on gold. The fundamental reasons for this evolution and the problems raised by the present situation are emphasized.